O discurso do cidadão de bem e a lógica do supereu - Albuquerque Junior, Artur Julio de (2018)
This research had aimed, based on the logic of the obsessional neurosis, to reach a movement that allows us to think about the aspects that underlie the social speech, that we allegorically called the ‘good citizen’s speech’. The method used corresponds to the concept of “support” that Freud’s works with, in order to sustain the idea that the sexual drives are initially supported by instincts, to only then acquire autonomy. Thus, we initially lean in the structural mechanism of obsessional neurosis, and later ascend to the scope of the social problem, where we underline the reactive figure of the good citizen. As a result of this path, we achieved an articulation between the discursive dimension of the good citizen with the paradoxical dialectic of the superego, that encloses the regime of the law at the same time that safeguards our most basic constitution in a statute completely outside the law. Finally, we analyze the effects of this situation from some social reactions to two events from the field of art, which are: the exhibition “Queermuseu” and “La Bête” performance. We emphasize that the claims of the good citizen that propose the protection of family, morals and decency, denounce the impetus of these subjects, in overcoming the conditions of their own ideals.